Cellular and molecular control of mating in male C. elegans - Garcia, L. Rene (Henry Stewart Talks, 2010)
A neuro-muscular circuit that mediates goal-oriented behavior, Cholinergic regulation of motor outputs, Genetics of CaMKII and ERG K+ channel control of behavioral states, Integration of copulation and food signals in cell excitability, The effect of nutrition and aging on behavioral decay